2020
DOI: 10.1039/c9sm02483b
|View full text |Cite
|
Sign up to set email alerts
|

An eco-friendly pathway to thermosensitive micellar nanoobjects via photoRAFT PISA: the full guide to poly(N-acryloylpyrrolidin)-block-polystyrene diblock copolymers

Abstract: Spherical macromolecular assemblies, so-called latexes, consisting of polystyrene (PS) resemble a relevant class of synthetic polymers used for a plethora of applications ranging from coatings or lubricants to biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 66 publications
2
20
0
Order By: Relevance
“…13 Nowadays, the combination of RDRP methods with emulsion or dispersion polymerization techniques is a feasible approach to produce research and industrially relevant copolymers with predetermined molecular weights and architectures. 16,17 These methods provide efficient heat transfer, low viscosity during the entire reaction time and enable the production of well-defined polymers. 14,[16][17][18] Dispersion polymerization initially involves a completely homogeneous solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Nowadays, the combination of RDRP methods with emulsion or dispersion polymerization techniques is a feasible approach to produce research and industrially relevant copolymers with predetermined molecular weights and architectures. 16,17 These methods provide efficient heat transfer, low viscosity during the entire reaction time and enable the production of well-defined polymers. 14,[16][17][18] Dispersion polymerization initially involves a completely homogeneous solution.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 These methods provide efficient heat transfer, low viscosity during the entire reaction time and enable the production of well-defined polymers. 14,[16][17][18] Dispersion polymerization initially involves a completely homogeneous solution. [19][20][21][22] However, the resultant polymer is not soluble in the polymerization medium.…”
Section: Introductionmentioning
confidence: 99%
“…[ 63,64 ] The polymerization of styrene via RAFT emulsion polymerization has been intensively studied by our group and has many advantages such as fast reaction rates, economically feasible reaction conditions, and high molar masses with narrow dispersity. [ 65,66 ] The synthesis of PS‐ b ‐PMAA has one additional advantage, that is, the diblock copolymer can be synthesized in a single batch as initially reported by the group of Charleux et al. for a similar polymer.…”
Section: Resultsmentioning
confidence: 99%
“…in a previous study. [ 40 ] In that work it was found that even a butyl group at the end of a via photoRAFT synthesized LCST polymer, poly( N ‐acryloylpyrrolidin), caused formation of micelles below T CP . In addition, these micelles with hydrophilic shells were well stabilized in water and could still be initiated by UV light for chain extensions.…”
Section: Methodsmentioning
confidence: 99%